The development of ENP board game as teaching aid in learning Dunia Seni Visual among year 2 student / Jannatul Farhana Mohd Jaafar - Mohd Jaafar, Jannatul Farhana (2014)
The purpose of this study was to see the development Element and Principle (ENP) board game as a teaching aid in the process of learning in Dunia Seni Visual subject among year 2 student. Looking ENP board game as a teaching aid in the process of learning in Dunia Seni Visual subject. In addition, it also see the effectiveness of ENP board game as a teaching aid in attracting student interest in the Dunia Seni Visual subject. The study was conducted at the Sekolah Kebangsaan Bandar Tun Hussein Onn, Cheras Selangor. The sample consisted of 10 students from year 2. The instrument was used to measure the effectiveness of ENP board game for students in the observation. Observation method was used in the process of collecting data for the study. The findings of the study show that there is a positive relationship between the uses of ENP board game as teaching aid in enhancing students' interest in the Dunia Seni Visual subject. Therefore, ENP board game as teaching aid is one way to attract students in Seni Visual Dunia subject.